Optimizing soil- and foliar-applied herbicides for weed management - Schroeder de Souza, Joana (My University, 2025)
Waterhemp (Amaranthus tuberculatus) has been a major challenge in the U.S in recent years, reducing soybean yields by as much as 56% when it emerges with the crop. In row-crop production systems, herbicides are often the best option for controlling weeds due to their relatively easy implementation. However, the extensive use of post-emergent herbicides, such as glyphosate, has led to the evolution of herbicide-resistant weed populations. To address these problems, soybean producers are once again utilizing soil-applied residual herbicides as part of their weed control programs, which offer multiple effective sites of action (SOA). The major objectives of this thesis were to 1) screen waterhemp populations from Northeast Kansas to confirm multiple herbicide resistance and investigate potential reduction in glufosinate sensitivity, 2) understand soybean tolerance to soil-applied herbicides, especially in the presence of soil variability, and 3) evaluate the weed control efficacy and droplet characteristics when adding different adjuvant combinations to herbicide products for burndown applications. Greenhouse screening experiments showed some waterhemp populations from Northeast Kansas with multiple resistance to fomesafen, lactofen, and glyphosate, while the dose-response study confirmed that four waterhemp populations were less sensitive to glufosinate. Results from the soil-applied herbicide study in the greenhouse showed that for sulfentrazone the interaction between soil texture, pH, and herbicide rate influenced soybean seedling emergence, and for chlorimuron-ethyl pH: texture and texture: rate were significant, indicating that the effect of pH on soybean seedling emergence depends on soil texture and that the impact of herbicide rate varies according to the soil texture. The field study showed that weed control can be optimized, including adjuvants to glyphosate and saflufenacil, among the different adjuvant types, the combination that had the best weed control for both herbicides was Amsol™ + Noble®. Enhancing our understanding of these factors will allow the optimization of weed control, helping to sustain chemical control as a critical component of integrated weed management programs.
Keywords: Waterhemp; Soybean; Resistance; Adjuvants